2008
DOI: 10.1590/s1516-31802008000600005
|View full text |Cite
|
Sign up to set email alerts
|

Safety in intrahospital transportation: evaluation of respiratory and hemodynamic parameters. A prospective cohort study

Abstract: CONTEXT AND OBJECTIVE: Intrahospital transportation of mechanically ventilated patients is a high-risk situation. We aimed to determine whether transfers could be safely performed by using a transportation routine. DESIGN AND SETTING:Prospective cohort study with "before and after" evaluation. METHODS:Mechanically ventilated patients who needed transportation were included. Hemodynamic and respiratory parameters were measured before and after transportation. Statistical analysis consisted of variance analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 24 publications
2
17
0
4
Order By: Relevance
“…(14,15) The organization of the transport of critically ill patients should be optimized from planning to execution. It is essential to define the components of the team and the number of professionals needed according to the clinical condition of the patient, but there must be at least two members, one being the nurse of the intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
“…(14,15) The organization of the transport of critically ill patients should be optimized from planning to execution. It is essential to define the components of the team and the number of professionals needed according to the clinical condition of the patient, but there must be at least two members, one being the nurse of the intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
“…2,13,[16][17][18]21 Human-based mishaps develop from inadequate training, monitoring, and communication. 5,17,18 Inadequate communication may cause a delay in procedures, potentially compromising safety and resuscitation of patients. 7,9,10,14,18 Suboptimal monitoring and agitation of the patient may result in unplanned extubation.…”
Section: Systems-based Mishapsmentioning
confidence: 99%
“…5,7,11,19,21,23,[26][27][28][29]39 Lahner et al 25 reports that anesthesiologists perform all transports; nurses do not routinely accompany patients during transport. Winter 40 recommends that an intrafacility transport be delayed until an adequately trained physician is present.…”
Section: Discussionmentioning
confidence: 99%
“…5,[24][25][26][27][28] This wide variation is largely based on differences in definitions of adverse events. As an example, in the study by Kue et al, 24 who reported an overall adverse event rate of 1.7%, technical events such as losing an intravenous catheter or equipment malfunction were excluded as adverse events.…”
Section: Adverse Events During Transportmentioning
confidence: 99%
See 1 more Smart Citation